Glucagonoma and Glucagonoma Syndrome: A Case Report with Review of Recent Advances in Management - Ashraf Al-Faouri; Khaled Ajarma; Samer Alghazawi; Sura Al-Rawabdeh; Adnan Zayadeen (Case Reports in Surgery, 2016)
The rarity of glucagonoma imposes a challenge with most patients being diagnosed after a long period of treatment for their skin rash (months-years). Awareness of physicians and dermatologists of the characteristic necrolytic migratory erythema often leads to early diagnosis. Early diagnosis of glucagonoma even in the presence of resectable liver metastases may allow curative resection. Herein, we present a typical case of glucagonoma treated at our center and review the literature pertinent to its management.